Relationship of Trade Openness, Financial Openness, and Unemployment Rate in ASEAN - Alvin Sugeng Prasetyo; Zaka Amar M (Jurusan Ilmu Ekonomi Fakultas Ekonomi Universitas Trunojoyo Madura, 2022)
This study discusses the role of economic globalization in reducing unemployment in ASEAN. The purpose of this study is to test and analyze the effect of economic globalization on unemployment in ASEAN. The method used is GMM with the period 1996-2021. Estimation results indicate that economic growth and inflation have a significant negative effect on the unemployment rate in ASEAN, while economic globalization and trade openness have a significant positive effect on unemployment in ASEAN, but financial risk does not have a significant effect on unemployment in ASEAN. Keyword: GMM, Unemployment, Economic Growth, Inflation, Economic Globalization, Trade Openness, Financial Openness